Nomograms for Predicting Axillary Lymph Node Status Reconciled With Preoperative Breast Ultrasound Images - Liu, Dongmei; Lan, Yujia; Zhang, Lei; Wu, Tong; Cui, Hao; Li, Ziyao; Sun, Ping; Tian, Peng; Tian, Jiawei; Li, Xia (Frontiers in Oncology, 2021)
Introduction: The axillary lymph node (ALN) status of breast cancer patients is an important prognostic indicator. The use of primary breast mass features for the prediction of ALN status is rare. Two nomograms based on preoperative ultrasound (US) images of breast tumours and ALNs were developed for the prediction of ALN status. Methods: A total of 743 breast cancer cases collected from 2016 to 2019 at the Second Affiliated Hospital of Harbin Medical University were randomly divided into a training set (n=523) and a test set (n=220). A primary tumour feature model (PTFM) and ALN feature model (ALNFM) were separately generated based on tumour features alone, and a combination of features was used for the prediction of ALN status. Logistic regression analysis was used to construct the nomograms. A receiver operating characteristic curve was plotted to obtain the area under the curve (AUC) to evaluate accuracy, and bias-corrected AUC values and calibration curves were obtained by bootstrap resampling for internal and external verification. Decision curve analysis was applied to assess the clinical utility of the models. Results: The AUCs of the PTFM were 0.69 and 0.67 for the training and test sets, respectively, and the bias-corrected AUCs of the PTFM were 0.67 and 0.67, respectively. Moreover, the AUCs of the ALNFM were 0.86 and 0.84, respectively, and the bias-corrected AUCs were 0.85 and 0.81, respectively. Compared with the PTFM, the ALNFM showed significantly improved prediction accuracy (p<0.001). Both the calibration and decision curves of the ALNFM nomogram indicated greater accuracy and clinical practicality. When the US tumour size was ≤21.5 mm, the Spe was 0.96 and 0.92 in the training and test sets, respectively. When the US tumour size was greater than 21.5mm, the Sen was 0.85 in the training set and 0.87 in the test set. Our further research showed that when the US tumour size was larger than 35 mm, the Sen was 0.90 in the training set and 0.93 in the test set. Conclusion: The ALNFM could effectively predict ALN status based on US images especially for different US tumour size.